If it's not what You are looking for type in the equation solver your own equation and let us solve it.
314=13(x-2)-(12x-13)+2(150+x)
We simplify the equation to the form, which is simple to understand
314=13(x-2)-(12x-13)+2(150+x)
Reorder the terms in parentheses
314=+(+13x-26)-(12x-13)+2*(150+x)
Remove unnecessary parentheses
+314=+13x-26-(+12x-13+)+2+*(+150+x+)
Remove unnecessary parentheses
314=+13x-26-12x+13+2*(150+x)
Reorder the terms in parentheses
314=+13x-26-12x+13+(+300+2x)
Remove unnecessary parentheses
+314=+13x-26-12x+13+300+2x
We move all terms containing x to the left and all other terms to the right.
-13x+12x-2x=-26+13+300-314
We simplify left and right side of the equation.
-3x=-27
We divide both sides of the equation by -3 to get x.
x=9
| 8t-2=16(t-2.5) | | 2+2y=-6 | | 4x+3=12x-13 | | 1+3x=16-2r | | 6+9x=8x-12 | | 12h=10h | | 3-4x=44 | | 56x+2=42x+5 | | 5-8x=24 | | 4x-25=105 | | 5x-9=13x-(8x-4) | | 2x-4-5x+10=40 | | 3x+17=59 | | 4(2m+1)=3(2m-5) | | 40x+40=15x+30 | | 3x(2x-1)(x^2-9)(x^2+8)=0 | | 5x^2=3y | | 4x=22x+56 | | -8=32-8q | | 10(3-x)-4(6-8x)+1,5(4-10x)-26=0 | | 30-12x=26+4x | | 4t^2+7t-15=0 | | 4(2x-3)=23 | | 12z+7=67+9z | | 4(h-7)+4=-8 | | 2(c+10)-9=7 | | 5t-7+9t=4t-33 | | 6m-2=19-m | | 5(h-1)+6=-9 | | 2(w+5)-1=5 | | -4(s-6)-3=9 | | -(b-9)+2=3 |